Ultrahigh Permeability at High Frequencies via A Magnetic-Heterogeneous Nanocrystallization Mechanism in an Iron-Based Amorphous Alloy - Zhou, Jing (Advanced materials (Deerfield Beach, Fla.), 2023)
© 2023 Wiley-VCH GmbH.